Numerous Vascular Malformations in Orofacial Region – A Diagnostic and Therapeutic Challenge - Debasish Pramanick (Journal of Orofacial Research, 2021)
Vascular lesions always remain a challenge as far as its diagnosis and treatment are concerned because of its close proximity tovital structures and risk of severe hemorrhage. Different types of vascular lesions like hemangiomas, vascular malformationsare often encountered in day-to-day dental practice, but presence of multiple vascular lesions in the orofacial region is quiterare. Here, a rare and interesting case of multiple vascular malformations in the head-neck region of a 39-year-old femalepatient involving the tongue, cheeks, lips, palate and eyes has been reported. After getting prior informed consent and routinepreoperative haematological investigations, an incisional biopsy was done from the buccal mucosal lesion and tongue lesion.Histopathological examination of the biopsied samples revealed the presence of non-dysplastic, parakeratinized stratifiedsquamous epithelium backed by connective tissue stroma. The stroma contains numerous vascular channels containing redblood corpuscles within. No active endothelial proliferation was noted. Sprinkling of chronic inflammatory cells was alsonoted. Based on the said histopathological features, a diagnosis of vascular malformation was confirmed. Proper diagnosis andmaking differentiation between haemangiomas and vascular malformations is utmost important because of their differenttreatment plan.